ANALISIS KEBERHASILAN PENERAPAN PERATURAN WALI KOTA PALU NOMOR 40 TAHUN 2021 TENTANG PEMBATASAN PENGGUNAAN KEMASAN PLASTIK SEKALI PAKAI DAN STYROFOAM - Siti Rahmatia Pratiwi; Awwalini Maghfirah Salim; Darasita Zahra Dayanun; Anita Pratiwi; Ardini Wulandari; Fatimah Maulida (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
Environmental pollution issue from solid waste, especially plastic, is a global concern because it harms ecosystems and human health. A major cause is the use of single-use plastics and styrofoam, which do not break down easily. In Palu City, this problem led to the issuance of Palu Mayor Regulation Number 40 of 2021 concerning the Restriction on the Use of Single-Use Plastic Packaging and Styrofoam. This study evaluates how well this policy has been implemented and its effect on reducing plastic waste. Using descriptive quantitative methods to analyze secondary data of waste generation and achievements in waste handling from the National Waste Management Information System (SIPSN) for the years preceding (2020) and following (2024) the regulation’s implementation. The results show a significant drop in plastic waste from 30.00% to 10.43%, along with decreases in daily and yearly waste amounts. The recycling rate also improved from 0.51 to 0.58, indicating an improvement in waste management, especially through the use of TPS3R. The study recommends stronger public education, better monitoring, and improved facilities to ensure the policy’s success and sustainability in Palu City.